2018
DOI: 10.1177/0013916517749876
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relation of Spatial Access to Fast Food Outlets With Body Weight: A Mediation Analysis

Abstract: We examined explanatory pathways for the association between spatial access to fast food outlets and body weight in 5,076 European adults (18+). The total effect of spatial access to fast food outlets on self-reported weight status was examined using regression analyses accounting for clustering at the neighborhood level. Perceived availability and usage of fast food outlets, and fast food consumption, were considered as potential mediators and age, gender, socioeconomic status, and urban region as potential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 56 publications
1
25
0
4
Order By: Relevance
“…Our study may lack power to detect such distal effects or unobserved effects or a suppressor variable could be operating. 23 However, previous studies detecting associations may result from residual confounding through social disadvantage; these associations are consistent throughout the literature between location of fast-food outlets and deprivation 6 and between deprivation and BMI. 24 25 This suggests that focusing on the role of social disadvantage rather than the fast-food outlets may yield more effective policy gains.…”
Section: Discussionsupporting
confidence: 82%
“…Our study may lack power to detect such distal effects or unobserved effects or a suppressor variable could be operating. 23 However, previous studies detecting associations may result from residual confounding through social disadvantage; these associations are consistent throughout the literature between location of fast-food outlets and deprivation 6 and between deprivation and BMI. 24 25 This suggests that focusing on the role of social disadvantage rather than the fast-food outlets may yield more effective policy gains.…”
Section: Discussionsupporting
confidence: 82%
“…Increasing our understanding of the mechanisms through which the physical and social neighbourhood environment may influence body weight and obesity is crucial to effectively combat the current obesity epidemic [4]. There is some evidence that physical neighbourhood environmental characteristics such as limited access to sidewalks [5, 6], low aesthetics [5], low walkability areas [7, 8], larger distance to recreational facilities [6, 9] and higher fast food density [10, 11] are linked to higher body weights and obesity [12, 13]. Conversely, one longitudinal study conducted in Canada found that higher neighbourhood walkability was associated with lower prevalence of overweight and obesity [14].…”
Section: Introductionmentioning
confidence: 99%
“…The impossibility of using data related to school and workplace food environment is a limitation, considering that 76.2% and 22.3% of the adolescents were studying and working, respectively (data not shown). As a result, adolescents may consume foods sold by food establishments beyond the vicinity of their homes, which might explain the lack of association with other establishments 60 . Therefore, the use of a 500m buffer near adolescents' residence may not be the best approach to assess their food environment.…”
Section: Discussionmentioning
confidence: 99%